Pengaruh Sikap Mengeluh Dan Ketidakpuasan Pada Perilaku Mengeluh Pembeli Sepeda Motor Yamaha - Nityawan, Putu Eka Dita; Ardani, I Gst Agung Ketut Sri (E-Jurnal Manajemen, 2015)
This study aims to determine the effect of dissatisfaction with the attitude of complaining and complaining behavior committed consumers who purchased a Yamaha motorcycle in the city of Denpasar. Sample size of 105 people with purposive sampling method. Data were collected by questionnaires that using 5-point Likert scale to measure the 15 indicators of the three variables of the study. The analysis technique used is multiple linear regression. This study obtain the result that the complaining attitude positive and significant effect on the behavior complained of and dissatisfaction positive and significant effect on the behavior complained.
Keywords: sikap mengeluh; ketidakpuasan; perilaku mengeluh